NuRD-dependent DNA methylation prevents ES cells from accessing a trophectoderm fate - Paulina A. Latos; Christine Helliwell; Olukunbi Mosaku; Dominika A. Dudzinska; Bryony Stubbs; Maria Berdasco; Manel Esteller; Brian Hendrich (Biology Open, 2012)
Summary Embryonic Stem (ES) cells are able to give rise to the three germ layers of the embryo but are prevented from contributing to the trophoblast. The molecular nature of this barrier between embryonic and trophectodermal cell fates is not clear, but is known to involve DNA methylation. Here we demonstrate that the Nucleosome Remodeling and Deacetylation (NuRD) co-repressor complex maintains the developmental barrier between embryonic and trophectodermal cell fates by maintaining transcriptional silencing of trophectoderm determinant genes in ES cells. We further show that NuRD activity facilitates DNA methylation of several of its target promoters, where it acts non-redundantly with DNA methylation to enforce transcriptional silencing. NuRD-deficient ES cells fail to completely silence expression of the trophectoderm determinant genes Elf5 and Eomes, but this alone is not sufficient to induce transdifferentiation towards the trophectoderm fate. Rather this leaves ES cells capable of activating expression of trophectoderm-specific genes in response to appropriate extracellular signals, enabling them to commit to a trophectodermal cell fate. Our findings clarify the molecular nature of the developmental barrier between the embryonic and trophoblast cell fates, and establish a role for NuRD activity in specifying sites for de novo DNA methylation.